Utilization of Indigofera (Indigofera zollingeriana) leaf meal in the ration on chemical meat composition, carcass and non-carcass production, and feces-derived methane yield of male growing rabbit - Sutaryo Sutaryo; Oktafia Munita Rahmawati; Subur Subur; Retno Adiwinarti; Endang Purbowati; Agung Purnomoadi (Livestock and Animal Research, 2022)
Objective: The aim of this study were to evaluate the inclusion of Indigofera leaf meal (ILM) in the ration on the carcass and non-carcass production, meat chemical composition and feces-derived methane yield of New Zealand White (NZW) rabbits.Methods: Twenty eights male NZW rabbits with initial body weight of 1455.25 ± 142.41 g, and 65-70 d old were used in this study. There were four treatments namely basal feed (T0); inclusion 4% (T1); 8% (T2), and 12% of ILM (T3) in the ration. The ration was made in form of pellet, and iso-protein that containing 16% of crude protein (CP). The observed variables were carcass and non-carcass production, meat nutrient content and feces-derived methane production.Results: The study result showed that inclusion of ILM in the rabbit ration up to 12% gave no significant effect (P>0.05) on the carcass and non-carcass production, nutrient content of the rabbit meat (CP, extract ether, moisture and ash) both in Longissimus dorsi (LD) and Bicep femoris (BF) muscles. The moisture concentration in LD muscle showed lower than that in BF muscle, while EE content of LD was higher than that in BF muscle. The result also showed that the incorporation of ILM in the ration up to 12% gave no significant effect (P>0.05) on the methane production of rabbit feces.Conclusions: The treatments gave no impact on the observed variables. Therefore, ILM can be used as a protein source in male growing rabbit ration at least up to 12%.